A Systematic Review of Flurbiprofen 8.75 mg Dose and Risk of Haemorrhagic Events - Dhanda, Sandeep; Evans, Alison; Roy, Debabrata; Osborne, Vicki; Townsley, Adam; Coutinho, Graça; Kulasekaran, Anuradha; Shakir, Saad (Frontiers in Pharmacology, 2021)
Oral non-steroidal anti-inflammatory drugs (NSAIDs) are known to be associated with an increased risk of bleeding. The NSAID, flurbiprofen, in the form of 8.75mg lozenge or oromucosal spray is indicated for the symptomatic relief of sore throat. Despite the low dose as compared to alternative flurbiprofen preparations, concerns have been raised regarding its safety in terms of haemorrhagic events. This systematic review was conducted to identify existing evidence on the risk of haemorrhagic events with flurbiprofen 8.75mg dose (any formulation), particularly where this may be due to potential interactions with other medicinal products. The systematic review examined studies reporting haemorrhagic events in patients receiving flurbiprofen 8.75mg dose. Six individual electronic databases were searched up to 28th April 2020. Records were initially screened for relevance followed by further review of potentially eligible studies. Data extraction was performed for eligible studies and risk of bias in studies was assessed. The search strategy identified 1093 individual records. Of these, 1038 records were excluded after initial review; the majority of these records related to flurbiprofen in alternative formulations with alternative doses (e.g., eye drops, skin patches, oral tablets) and thus were not considered relevant for further review. The 55 remaining records related to flurbiprofen 8.75mg dose (any formulation) or flurbiprofen lozenge/oromucosal spray where the dose was not specified. After further review, 52 of these records were not considered eligible. Thus, only three records were included in this systematic review. The three studies reported a total of five haemorrhagic events in patients taking flurbiprofen 8.75mg lozenge; the corresponding risk in each of the studies was 8.33%, 1.98% and 1.96%. Where possible, comparison of flurbiprofen 8.75mg lozenge to placebo produced risk ratios of 0.96 (95% CI 0.07, 13.25) and 2.00 (95% CI 0.10, 118.0). This systematic review suggests that haemorrhagic events do not appear to be a frequent complication of flurbiprofen when used at a dose of 8.75mg. Counts were low across all studies, however small study sample sizes yielded a common incidence (i.e., ≥1.0%). Results comparing flurbiprofen and placebo treatment arms were non-significant. Findings from this systematic review did not suggest haemorrhagic safety concerns.